Profitability Effect Performance and Eco-Efficiency on Company Value using ESG as A Moderation Variable (Study on Energy Sector Companies on The Indonesia Stock Exchange) - Prastiwi Puspa Ningrum; Yosefa Sayekti; Ririn Irmadariyani (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
The increasing demand for sustainable business practices has encouraged companies to consider not only financial performance but also environmental responsibility and governance quality in creating long-term corporate value. The energy sector, as one of the industries with significant environmental impacts, faces challenges in maintaining profitability while implementing sustainability strategies. This study aimed to examine the effects of profitability and eco-efficiency on company value and to analyze the role of Environmental, Social, and Governance (ESG) as a moderating variable in these relationships. This research employed a quantitative approach using a causal associative design. Data were obtained from annual reports and sustainability reports of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. Using purposive sampling, 215 firm-year observations were selected and analyzed through panel data regression using the Fixed Effects Model (FEM) and Moderated Regression Analysis (MRA). The results showed that profitability had a positive and significant effect on company value, whereas eco-efficiency did not significantly influence company value. Furthermore, ESG strengthened the relationship between profitability and company value, indicating that sustainability disclosures enhanced market recognition of financial performance. However, ESG did not moderate the relationship between eco-efficiency and company value. This study concluded that profitability remained a key determinant of corporate value, while sustainability practices required stronger market recognition to generate valuation benefits. The findings provide implications for companies, investors, and policymakers in developing sustainable strategies that integrate financial performance with ESG principles.